Análise da gestão institucional na Universidade Estadual de Goiás segundo indicadores quantitativos de desempenho - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
In the “knowledge society” the role and function of the University has been reframed as the use of knowledge is linked to meeting the demands of neoliberal capitalism as a contemporary hegemonic system. In addition, the current national public policy of opening to commercialization has transformed non-free higher education into a semi-commodity for the private sector in view of its diffusion and massification. In this context, the objective of the research was to assess the historical panorama of institutional management at the State University of Goiás (UEG) in the years 2011 to 2018, according to performance indicators in terms of transparency and their economic, social and environmental impacts, since UEG represents the only public and free institution maintained by the state government of Goiás. The analysis methodology is characterized as exploratory-descriptive with documentary sources and, for data collection, we use the Access to Information Law nº 12.527/2011 (LAI). In the processing, the principles of descriptive statistics were used, in order to show the analysis of historical, average and percentage quantitative values in graphs, figures and tables. As main results, in relation to transparency, it was found that UEG promotes the process of publicizing information of a public nature, as well as complying with the deadlines established by LAI. Regarding social indicators, we found that UEG lost space in the number of students in relation to the private network in the state. In another aspect, it improved the qualification of the faculty and reduced the numerical difference between permanent and temporary employees. At the economic level, we note that the delicate financial situation of the institution, as the significant increase in expenses, leveraged mainly by the payroll, was not accompanied by the increase in revenues. At the environmental level, we verified the total ignorance of knowledge and the absence of actions to mitigate the impacts on the environment in which it operates. We conclude that it is essential to permanently monitor and analyze public policies linked to UEG to verify the current level of its management and, thus, reduce or mitigate the negative aspects and enhance the assertive aspects in the consolidation of the State Education Plan for higher education in Goiás.
Analysis of institutional management at the State University of Goiás according to quantitative performance indicators
Keywords: Universidade Estadual de Goiás; Gestão Institucional; Indicadores de desempenho; Panorama Histórico; Lei de Acesso à Informação; State University of Goiás; Institutional Management; Performance Indicators; Historical Overview; Law of Access to Information; OUTROS